Appraisal of systematic reviews on interventions for postpartum depression: systematic review - Chow, Ryan (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Postpartum depression (PPD) is a highly prevalent mental health problem that affects parental health with implications for child health in infancy, childhood, adolescence and beyond. The primary aim of this study was to critically appraise available systematic reviews describing interventions for PPD. The secondary aim was to evaluate the methodological quality of the included systematic reviews and their conclusions. METHODS: An electronic database search of MEDLINE, Embase, and the Cochrane Library from 2000 to 2020 was conducted to identify systematic reviews that examined an intervention for PPD. A Measurement Tool to Assess Systematic Reviews was utilized to independently score each included systematic review which was then critically appraised to better define the most effective therapeutic options for PPD. RESULTS: Of the 842 studies identified, 83 met the a priori criteria for inclusion. Based on the systematic reviews with the highest methodological quality, we found that use of antidepressants and telemedicine were the most effective treatments for PPD. Symptoms of PPD were also improved by traditional herbal medicine and aromatherapy. Current evidence for physical exercise and cognitive behavioural therapy in treating PPD remains equivocal. A significant, but weak relationship between AMSTAR score and journal impact factor was observed (p = 0.03, r = 0.24; 95% CI, 0.02 to 0.43) whilst no relationship was found between the number of total citations (p = 0.27, r = 0.12; 95% CI, − 0.09 to 0.34), or source of funding (p = 0.19). CONCLUSION: Overall the systematic reviews on interventions for PPD are of low-moderate quality and are not improving over time. Antidepressants and telemedicine were the most effective therapeutic interventions for PPD treatment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12884-020-03496-5.